Supporting Distributed Feed-Following Apps over Edge Devices - Chandramouli, Badrish; Nath, Suman; Zhou, Wenchao (2012)
In feed-following applications such as Twitter and Facebook, users (consumers) follow a large number of other users (producers) to get personalized feeds, generated by blending producers' feeds. With the proliferation of Cloud-connected smart edge devices such as smartphones, producers and consumers of many feed-following applications reside on edge devices and the Cloud. An important design goal of such applications is to minimize communication (and energy) overhead of edge devices. In this paper, we abstract distributed feed-following applications as a view maintenance problem, with the goal of optimally placing the views on edge devices and in the Cloud to minimize communication overhead between edge devices and the Cloud. The view placement problem for general network topology is NP Hard; however, we show that for the special case of Cloud-edge topology, locally optimal solutions yield a globally optimal view placement solution. Based on this powerful result, we propose view placement algorithms that are highly efficient, yet provably minimize global network cost. Compared to existing works on feed-following applications, our algorithms are more general - they support views with selection, projection, correlation (join) and arbitrary black-box operators, and can even refer to other views. We have implemented our algorithms within a distributed feed-following architecture over real smartphones and the Cloud. Experiments over real datasets indicate that our algorithms are highly scalable and orders-of-magnitude more efficient than existing strategies for optimal placement. Further, our results show that optimal placements generated by our algorithms are often several factors better than simpler schemes.